Two new species of the genus Allochotes (Coleoptera: Cleridae: Neorthopleurinae) from Taiwan - Murakami, Hiroyuki; Yamasako, Junsuke (Zootaxa, 2012)
Two new species of the genus Allochotes which have remarkable marking on elytra, A. choui sp. nov. and A. yichei sp. nov., are described from Taiwan. The aedeagus in an inflated condition is considered a worthy characteristic for the taxonomic study of the genus and a method for the observation of an inflated aedeagus is introduced.